2009
DOI: 10.1172/jci36230
|View full text |Cite
|
Sign up to set email alerts
|

PICK1 deficiency causes male infertility in mice by disrupting acrosome formation

Abstract: Protein interacting with C kinase 1 (PICK1) is a peripheral membrane protein involved in protein trafficking, a function that has been well characterized in neurons. Here, we report that male mice deficient in PICK1 are infertile and have a phenotype resembling the human disease globozoospermia. The primary defect in the testes of Pick1-knockout mice was fragmentation of acrosomes in the early stages of spermiogenesis. This fragmentation was followed by defects in nuclear elongation and mitochondrial sheath fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
149
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(155 citation statements)
references
References 40 publications
5
149
0
1
Order By: Relevance
“…A significant number of apoptotic cells were found in TNAPAtg7 −/− mouse testes compared with those in the Atg7 Flox/ Flox mice (Supplementary information, Figure S1A). These results are consistent with a previous report [11] and suggest that those vacuoles might come from dead germ cells. However, even in the testis of the TNAPAtg7 −/− mice, no more than 0.5% of the germ cells died by apoptosis (Supplementary information, Figure S1B).…”
Section: Germ Cell-specific Knockout Of Atg7 Causes Male Infertility supporting
confidence: 94%
See 1 more Smart Citation
“…A significant number of apoptotic cells were found in TNAPAtg7 −/− mouse testes compared with those in the Atg7 Flox/ Flox mice (Supplementary information, Figure S1A). These results are consistent with a previous report [11] and suggest that those vacuoles might come from dead germ cells. However, even in the testis of the TNAPAtg7 −/− mice, no more than 0.5% of the germ cells died by apoptosis (Supplementary information, Figure S1B).…”
Section: Germ Cell-specific Knockout Of Atg7 Causes Male Infertility supporting
confidence: 94%
“…The results of histology study showed that although the diameters of round seminiferous tubules in TNAP-Atg7 −/− mice were comparable to those in Atg7 Flox/ Flox mice ( Figure 1E), a substantial portion of the tubule structure was disorganized with large vacuoles in TNAPAtg7 −/− compared with the normal seminiferous tubules in the Atg7 Flox/Flox male siblings ( Figure 1F and 1G). Those vacuoles in the tubule lumens usually come from dead germ cells [11]. We next used terminal deoxynucleotidyl transferase dUTP nick end labeling assay to investigate whether there was apoptosis in those germ cells.…”
Section: Germ Cell-specific Knockout Of Atg7 Causes Male Infertility mentioning
confidence: 99%
“…PICK1 is a scaffold protein to control trafficking of several membrane receptors, including AMPA receptor and ASIC, and has been implicated to function in nervous system and male fertility [17,19,20,42]. Here, we identify PICK1 as a novel negative regulator of TGF-β signaling by modulating subcellular localization and trafficking of TβRI.…”
Section: Discussionmentioning
confidence: 93%
“…Pick1 -/-mice have been reported [42]. MEFs were isolated and cultured as previously described [51].…”
Section: Pick1 -/-Mice and Mef Isolationmentioning
confidence: 99%
“…Indeed, the SPATA16 protein localizes to the Golgi apparatus and the proacrosomal granules that are transported in the acrosome in round and elongated spermatids [41]. Pick1 localizes to Golgi-derived proacrosomal granules and is involved in vesicle trafficking from the Golgi to the acrosome and participates in acrosome biogenesis [42].…”
Section: Molecular Genetic Studiesmentioning
confidence: 99%